2016
DOI: 10.1002/cpmc.20
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Low‐Cost Procedure for Growing Geobacter sulfurreducens Cell Cultures and Biofilms in Bioelectrochemical Systems

Abstract: Anaerobic microorganisms play a central role in several environmental processes and regulate global biogeochemical cycling of nutrients and minerals. Many anaerobic microorganisms are important for the production of bioenergy and biofuels. However, the major hurdle in studying anaerobic microorganisms in the laboratory is the requirement for sophisticated and expensive gassing stations and glove boxes to create and maintain the anaerobic environment. This appendix presents a simple design for a gassing station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We grew WT cultures using anodes of microbial fuel cells as the sole electron acceptors (O'Brien and Malvankar, 2017). These growth conditions promote production of conductive biofilms and filaments as well as overexpression of PilA in comparison with growth on soluble electron acceptors such as fumarate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We grew WT cultures using anodes of microbial fuel cells as the sole electron acceptors (O'Brien and Malvankar, 2017). These growth conditions promote production of conductive biofilms and filaments as well as overexpression of PilA in comparison with growth on soluble electron acceptors such as fumarate.…”
Section: Resultsmentioning
confidence: 99%
“…The Geobacter sulfurreducens wild-type (WT) strain PCA (designated DL-1) (ATCC 51573, DSMZ 12127) (Coppi et al, 2001) and the omcS deletion mutant strain ) (designated DomcS) were obtained from our laboratory culture collection. The cultures were maintained at 30 C or at 25 C under strictly anaerobic conditions in growth medium supplemented with acetate (10 mM) as the electron donor and fumarate (40 mM) as the electron acceptor in sterilized and degassed NBAF medium (O'Brien and Malvankar, 2017). 1L NBAF medium contained the following: 0.04 g/L calcium chloride dihydrate, 0.1 g /L, magnesium sulfate heptahydrate, 1.8 g/L sodium bicarbonate, 0.5 g/L sodium carbonate, 0.42 g/L potassium phosphate monobasic, 0.22 g/L potassium phosphate dibasic, 0.2 g/L ammonium chloride, 0.38 g/L potassium chloride, 0.36 g/L sodium chloride, vitamins and minerals as listed in (O'Brien and Malvankar, 2017).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…1b , Extended Data Fig. 2e ) 13 . We found that G. sulfurreducens WT (DL1) strain primarily makes OmcS nanowires whereas strain W51W57 overexpresses OmcZ ( Extended Data Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Therefore, unless otherwise noted, WT strain was used to focus on studies of OmcS nanowires whereas W51W57 strain was used to focus on studies of OmcZ nanowires. As described previously 4 , the cells were grown in sterilized and degassed NBAF medium 13 , and 1L NBAF medium contained the following: 0.04 g/L calcium chloride dihydrate, 0.1 g/L magnesium sulphate heptahydrate, 1.8 g/L sodium bicarbonate, 0.5 g/L sodium carbonate, 0.42 g/L potassium phosphate monobasic, 0.22 g/L potassium phosphate dibasic, 0.2 g/L ammonium chloride, 0.38 g/L potassium chloride, 0.36 g/L sodium chloride, vitamins and minerals as listed in 13 . Resazurin was omitted and 1 mM cysteine was added as an oxygen scavenger.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation